Transmission and regulation of biochemical stimulus via a nanoshell directly adsorbed on the cell membrane to enhance chondrogenic differentiation of mesenchymal stem cell. Issue 1 (8th October 2019) - Han, Uiyoung; Hwang, Jun‐Ha; Lee, Jong‐Min; Kim, Hyeoni; Jung, Han‐Sung; Hong, Jeong‐Ho; Hong, Jinkee
Abstract: A nanoscale artificial extracellular matrix (nanoshell) formed by layer‐by‐layer adsorption can enhance and modulate the function of stem cells by transferring biochemical stimulus to the cell directly. Here, the nanoshell composed of fibronectin (FN) and chondroitin sulfate (CS) is demonstrated to promote chondrogenic differentiation of mesenchymal stem cells (MSCs). The multilayer structure of nanoshell is formed by repeating self‐assembly of FN and CS, and its thickness can be controlled through the number of layers. The expression of chondrogenic markers in MSCs coated with the FN/CS nanoshell was increased as the number of bilayers in the nanoshell increased until four, but when it exceeds five bilayers, the effect began to decrease. Finally, the MSCs coated with optimized four bilayers of FN/CS nanoshell have high chondrogenic differentiation efficiency and showed the potential to increase formation of cartilage tissue when it is transplanted into mouse kidney. So, the precise regulation of stem cell fate at single cell level can be possible through the cellular surface modification by self‐assembled polymeric film. Abstract : The nanoshell consisting of fibronectin and chondroitin sulfate directly adsorbed on cellular membrane enhances chondrogenic differentiation of mesenchymal stem cell and the efficiency of the chondrogenic differentiation was dependent on the number of layers in the nanoshell. This work suggests that carefully designed cellular nano‐environment could regulate stem cell fates.